Novel 2-(ω-phosphonooxy-2-oxaalkyl)acrylate monomers for self-etching self-priming one part adhesive - Klee, Joachim E (Beilstein-Institut, 2010)
Novel hydrolysis stable 2-(ω-phosphonooxy-2-oxaalkyl)acrylate monomers 3 with phosphoric acid moieties were synthesized by a three step synthesis via Baylis–Hillman reaction of ethyl acrylate and formaldehyde, and subsequent etherification of the obtained product with diols and phosphorylation using POCl(3). The polymerization enthalpy of 2-(ω-phosphonooxy-2-oxaalkyl)acrylates 3 as measured by DSC ranges from −29 to −53 kJ·mol(−1). The shear bond strength of adhesive compositions 4, comprising of polymerizable acids 3, ranges from 5.8 to 19.3 MPa on enamel and from 8.7 to 16.9 MPa on dentin.